EXPLORING THE ROLE OF INTERACTIVE RELIGIOUS ART IN FOSTERING MORAL REFORMATION AMONG STUDENT CULTISTS IN NIGERIAN HIGHER EDUCATION INSTITUTIONS - Bazunu , Harrie; Edo , Patience; Ottuh, Peter (Metafora: Education, Social Sciences and Humanities Journal, 2025)
This paper examines the utilization of interactive religious art to disseminate moral teachings and foster a sense of social responsibility among student cultists in Nigerian higher educational institutions. It expands the current literature by examining art as a medium for moral reformation. It addresses a geographical deficiency in Nigerian higher educational institutions, specifically those governed by the Nigerian government. Through extant literature, observations, and interviews, this research employs a mixed-methods approach to evaluate the efficacy of interactive religious art in fostering moral behaviour among Nigerian student cultists. The study indicates that interactive religious art can significantly contribute to moral reforming among student cultists by offering a distinctive and compelling platform for reflections, dialogue, and transformation. It is recommended that future research should investigate the impact that interactive religious artwork has on moral regeneration among a wide range of demographics, such as cultists, students in secondary school, employees of the civil service, and younger people.